2009
DOI: 10.1111/j.1939-1676.2009.0280.x
|View full text |Cite
|
Sign up to set email alerts
|

Ionized Hypocalcemia in Critically Ill Dogs

Abstract: Background: Ionized hypocalcemia (iHCa) is a common electrolyte disturbance in critically ill people, especially those with sepsis. The cause of the iHCa is not entirely understood and is likely multifactorial. Critically ill people with iHCa have longer hospital stays and higher mortality rates compared to people with normocalcemia. There are no published clinical studies evaluating the incidence and impact of iHCa in critically ill dogs.Hypothesis: iHCa occurs in critically ill dogs, is more prevalent in dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…To date, veterinary studies investigating the incidence and etiology of iHCa in dogs with traumatic injuries and its impact on morbidity and mortality have not been reported. A prospective study investigating iCa in critically ill dogs demonstrated a 16% incidence of iHCa; 13 dogs admitted for traumatic injuries were included but those dogs did not have an increased incidence of iHCa compared to other dogs in the study …”
Section: Introductionmentioning
confidence: 99%
“…To date, veterinary studies investigating the incidence and etiology of iHCa in dogs with traumatic injuries and its impact on morbidity and mortality have not been reported. A prospective study investigating iCa in critically ill dogs demonstrated a 16% incidence of iHCa; 13 dogs admitted for traumatic injuries were included but those dogs did not have an increased incidence of iHCa compared to other dogs in the study …”
Section: Introductionmentioning
confidence: 99%
“…Decreased calcium has also been documented in dogs with acute pancreatitis and has been suggested to carry a poorer prognosis. 7,8 Many dogs with acute pancreatitis have gross lipemia, whether as a cause or consequence of the disease (Fig. 3).…”
Section: Routine Clinical Pathologymentioning
confidence: 98%
“…The measuring of ionized calcium must be performed exclusively with heparinized total blood or plasma samples for describes (Holowaychuk et al, 2009). The measuring of intact PTH was validated in both dogs and cats, and it is extremely useful in the diagnosis of primary hypoparathyroidism, as well as for discarding other causes of hypocalcemia (Barber et al, 1993;Gear et al, 2005).…”
Section: Discussionmentioning
confidence: 99%